Delta-Omicron recombinant escapes therapeutic antibody neutralization - Ralf Duerr; Hao Zhou; Takuya Tada; Dacia Dimartino; Christian Marier; Paul Zappile; Guiqing Wang; Jonathan Plitnick; Sara B. Griesemer; Roxanne Girardin; Jessica Machowski; Sean Bialosuknia; et al. (iScience, 2023)
Summary: The emergence of recombinant viruses is a threat to public health, as recombination may integrate variant-specific features that together result in escape from treatment or immunity. The selective advantages of recombinant SARS-CoV-2 isolates over their parental lineages remain unknown. We identified a Delta-Omicron (AY.45-BA.1) recombinant in an immunosuppressed transplant recipient treated with monoclonal antibody Sotrovimab. The single recombination breakpoint is located in the spike N-terminal domain adjacent to the Sotrovimab binding site. While Delta and BA.1 are sensitive to Sotrovimab neutralization, the Delta-Omicron recombinant is highly resistant. To our knowledge, this is the first described instance of recombination between circulating SARS-CoV-2 variants as a functional mechanism of resistance to treatment and immune escape.